THE PSYCHOLOGICAL ASPECT OF THE SPECIFIC CHARACTERISTICS OF TEACHING MATHEMATICS IN HIGH SCHOOL - Rodica DRUȚA, Rodica (Acta et Commentationes, Sciences of Education, 2022)
In the digital age, the integration of information and communication technologies in the teaching of matematics in high school is a necessity. The correct integration of ICT, as a tool to ensure the efficiency of learning, requires a complex approach to the phenomenon from a psychological and pedagogical point of view, in order to identify the optimal conditions for integrating ICT in teaching mathematics in high school. This article is aimed at identifying the specific characteristics of teaching mathematics in high school from a psychological point of view, in order to outline an overview of the benefits of using ICT, but also the risks posed by the incorrect use of ICT in the mathematics instruction process.